ZIDOVUDINE: STRUCTURAL MODIFICATIONS AND THEIR IMPACT ON BIOLOGICAL ACTIVITIES AND PHARMACOKINETIC PROPERTIES - Noor Ul Amin Mohsin; Matloob Ahmed; Muhammad Irfan (Journal of the Chilean Chemical Society, 2019)
Zidovudine was the first drug approved for the treatment of Acquired Immuno Deficiency Syndrome (AIDS). Its chemical name is azidothymidine (AZT). AZTuse is associated with bone marrow toxicity. Shorter half-life and inability to penetrate the blood-brain barrier are the pharmacokinetic problems of this importantdrug molecule. Various modifications have been carried out in the structure of AZT. These include modification of hydroxyl and azido group, thymidine ring,preparation of phosphate and phosphonate derivatives, attachment of polymers and synthesis of hybrid molecules. Some of these changes produced compounds withsignificantly increased activity and less toxicity. This review highlights the various structural modifications of AZT and their influence on biological activities andpharmacokinetic properties.